Draw kawaii style : a beginner's step-by-step guide for drawing super-cute creatures, whimsical people, and fun little things - 62 lessons: basics, characters, special effects - Ranauro, Ilaria (Quarry Books, 2023)
"Draw Kawaii Style teaches the step-by-step fundamentals of drawing kawaii as well as how to illustrate specific characters and objects"--